WASTE MANAGEMENT PRACTICES AND ORGANIZATIONAL PERFORMANCE IN BEVERAGE MANUFACTURING FIRMS IN SOUTH-EAST NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
Waste Management Practices and Organizational Performance in Beverage Manufacturing Firms in South East Nigeria. With the growing concerns over environmental sustainability and corporate efficiency, waste management has become a critical focus in the manufacturing sector. This study investigates the effect of waste management practices on organizational performance in beverage manufacturing firms in South East Nigeria. The study seeks to find out specifically the effect of, waste recycling on organizational profitability and waste reduction on operational efficiency in beverage manufacturing firms in the region. Relevant conceptual, theoretical and empirical literature were reviewed, taking cognizance of the problem and hypothesis of the study. The study was anchored on Resource -Based View (RBV) theory developed by Wernerfelt (1996), which holds a reasonable explanation for the relationship that might exist between waste management and corporate sustainability. And also the theories of environmental sustainability by Robert Goodland (1995). Primary data was collected through survey method and interviews with managers and employees in selected beverage manufacturing firms. The population of the study comprised 2090 employees in selected Beverage Manufacturing firms in South-East Nigeria. A sample size of 408 was determined by using statistical formula devised by Borg and Gall (1973). The result showed that waste recycling had a significant positive effect on organizational profitability and this implies that firms with effective waste management strategies experience improved production process. Secondly, that Waste reduction had a significant positive effect on operational efficiency in beverage manufacturing firms in south-east Nigeria. The study concluded that waste management had a significant positive effect on organizational performance. This shows that the integration of efficient waste management systems not only contributes to environmental sustainability but also plays a pivotal role in enhancing the competitiveness and long term success of beverage manufacturing firms in south east Nigeria. Based on the findings, the study therefore recommended that Beverage manufacturing firms should formalize recycling initiatives as core components of their operational strategy as well as establish dedicated recycling units within the production plants to ensure systematic sorting, collection, and processing of recyclable materials, and that Beverage manufacturing firms should fully integrate Lean Manufacturing tools-such as 5S, kaizen, and Just-In-Time (JIT)- to systematically eliminate waste at every stage of production. This shows that waste management should be part of the organizations strategic goals by linking waste reduction targets with performance.